Management of a syphilis outbreak in street sex workers in east London. Issue 6 (28th June 2006) - Lomax, N; Wheeler, H; Anaraki, S; Anderson, H; Goh, B
Abstract : Objective: To describe the control and management of a syphilis outbreak in female street sex workers (SSWs) in east London. Methods: Following the identification of several cases of infectious syphilis in SSWs in east London, a targeted service for screening and treatment of syphilis and other sexually transmitted infections was developed. A multidisciplinary team (MDT) joined an existing outreach service to facilitate this. Once it became apparent that this was not an isolated case, an outbreak control team (OCT) was established. Results: Between April and December 2004 a total of 14 (58%) women with 15 cases of infectious syphilis were identified in 24 SSWs: 14/15 (93%) received treatment. Epidemiological treatment for syphilis was also given to the rest of SSWs at the initial visit. Several coexistent STIs were identified in this cohort. As part of the enhanced outbreak surveillance in north east London, 21 cases of infectious syphilis were reported in SSWs between April 2004 and December 2005. Conclusion: Outbreak management in this population was challenging: an MDT approach was crucial in identifying and treating syphilis to prevent onward transmission. There was a high prevalence of syphilis and other STIs in this cohort, and we treated the majority of cases. The formation of an OCT enabled us to monitor the outbreak and implement control measures more effectively. The novel intervention we describe has proved valuable in helping to control this syphilis outbreak.